In situ observation of the deterioration process of sulfide-based solid electrolytes using airtight and air-flow TEM systems. (22nd June 2021) - Tsukasaki, Hirofumi; Igarashi, Keisuke; Wakui, Akiko; Yaguchi, Toshie; Nakajima, Hiroshi; Kimura, Takuya; Sakuda, Atsushi; Tatsumisago, Masahiro; Hayashi, Akitoshi; Mori, Shigeo
Abstract: Sulfide-based solid electrolytes (SEs) exhibiting high ionic conductivity are indispensable battery materials for next-generation all-solid-state batteries. However, sulfide-based SEs have a major drawback in their low chemical stability in air. When exposed to H2 O or O2 gas, toxic H2 S is generated, and their ionic conductivity considerably declines. However, their degradation mechanism caused by air exposure has not been understood yet. To clarify the degradation process, in this study, we developed a transmission electron microscope (TEM) system to evaluate the air stability of battery materials. Using a vacuum transfer double-tilt TEM holder with a gas-flow system, the in situ observation of the degradation process was conducted for a sulfide-based Li4 SnS4 glass ceramic under an air-flow environment. Consequently, electron diffraction (ED) patterns and TEM images could clearly capture morphological changes and the amorphization process caused by air exposure. Moreover, based on the analysis of ED patterns, it is observed that Li4 SnS4 is likely to decompose because of the reaction with H2 O in air. Therefore, this airtight and air-flow TEM system should be effective in clarifying the process of the deterioration of sulfur-based SEs during exposure to air.